Seed production and quality in grafted cucumber - Claudio, M. T. R. [UNESP]; Nakada, P. G. [UNESP]; Tavares, A. E. B. [UNESP]; Magro, F. O. [UNESP]; Cardosoa, A. I. I. [UNESP]; Nascimento, W. M.; Silva, P. P.; Rosseto, M. (Int Soc Horticultural Science, 2019)
Even though there are many studies about grafting on vegetables, studies about seed production and quality of grafted plants are rarely found. Thus, the aim of this research was to evaluate the influence of different rootstock in grafted cucumber in seed production and quality. Five treatments were studied, one with ungrafted plants of cucumber and four grafted on different commercial pumpkin rootstock: T1 = cucumber line PEP 776, ungrafted plants; T2 = cucumber grafted on 'Shelper'; T3 = cucumber grafted on 'Exccite Ikky'; T4 = cucumber grafted on 'Keeper'; T5 = cucumber grafted on 'Tropical'. The experimental design used was randomized blocks, with four repetitions. There was no impact on seed production and quality by using a pumpkin rootstock, except for the 'Keeper' rootstock, which resulted in heavier fruits (533.6 g fruit(-1)) and higher seed production per fruit (3.82 g). There was no difference between ungrafted and grafted plants for weight of a 1000 seeds (average of 26.6 g), first count of standard germination test (average of 97.1%) and germination (average of 99.6%), showing that grafting did not affect seed quality.
Keywords: Cucumis sativus; Cucurbita; grafting; germination; rootstock